2018
DOI: 10.1558/jld.32226
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative investigation of the experience of accent stigmatisation among native and nonnative French speakers in Canada

Abstract: Decades of language attitudes research have documented negative evaluations of non-standard speakers. However, fewer studies have investigated the experience of stigmatization from the perspective of the non-standard speakers themselves. The study aims to explore the following questions: (1) What perception do speakers hold of their accent? (2) What does perceived accent discrimination look like? (3) How do stigmatized speakers respond to discriminatory experiences? Semistructured interviews were conducted amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…In French Canada specifically, a study by Noël and Beaton (2010) found that Acadian youth perceived that francophones from Quebec (a region in which French benefits from relatively higher vitality) evaluated the Acadian way of speaking as unacceptable, faulty, or shameful to the French language. In a qualitative study among French speakers from regions of varying levels of ethnolinguistic vitality, both nonnative and native participants reported experiencing accent discrimination in a broad range of settings (Freynet et al, 2018). This included differential treatment (e.g., being excluded, considered less suitable for employment, and treated with less respect), being singled out, or the perceived denial of French identity and competence.…”
Section: What Is the Meaning Of An Accent?mentioning
confidence: 99%
See 4 more Smart Citations
“…In French Canada specifically, a study by Noël and Beaton (2010) found that Acadian youth perceived that francophones from Quebec (a region in which French benefits from relatively higher vitality) evaluated the Acadian way of speaking as unacceptable, faulty, or shameful to the French language. In a qualitative study among French speakers from regions of varying levels of ethnolinguistic vitality, both nonnative and native participants reported experiencing accent discrimination in a broad range of settings (Freynet et al, 2018). This included differential treatment (e.g., being excluded, considered less suitable for employment, and treated with less respect), being singled out, or the perceived denial of French identity and competence.…”
Section: What Is the Meaning Of An Accent?mentioning
confidence: 99%
“…A study among minority Hungarian speakers learning Slovak as a second language in Slovakia supports this notion—it found that accent stigmatization was significantly and positively related to second language use anxiety (Vincze & MacIntyre, 2016). Among nonnative and native language speakers in French Canada, some described experiencing a decrease in their language confidence as a consequence of perceived discrimination (Freynet et al, 2018). Because reduced language confidence has previously been found to be related to unwillingness to communicate, weakened identity, and less language motivation, proficiency, and use of a language (Noels & Clément, 1996; Sampasivam & Clément, 2014; Vincze & MacIntyre, 2016), it is important to further understand factors that could lead to its loss.…”
Section: Language Confidence and Perceived Discriminationmentioning
confidence: 99%
See 3 more Smart Citations